1996
DOI: 10.1111/j.1523-5378.1996.tb00028.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Quadruple Therapy Using Lansoprazole, Instead of Omeprazole, in Curing Helicobacter pylori Infection

Abstract: The results with lansoprazole-quadruple therapy are comparable to the historic control group treated with omeprazole-quadruple therapy. The cure rare is very high, and although mild to moderate side effects occurred in many patients, everybody finished the treatment regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…When they increased the treatment period to seven days and used lansoprazole instead of omeprazole in 67 patients, the rates were 89 and 100% respectively. 37 Similar results were reported by Hosking et al 41 …”
Section: Therapiessupporting
confidence: 86%
“…When they increased the treatment period to seven days and used lansoprazole instead of omeprazole in 67 patients, the rates were 89 and 100% respectively. 37 Similar results were reported by Hosking et al 41 …”
Section: Therapiessupporting
confidence: 86%
“…In the mid-1990s, there were suggestions that only regimens which attained an eradication rate of 90% or more should be used in clinical practice [23][24][25]. In 1997, the cut-off between adequate and inadequate therapy was more clearly defined by the Maastricht conferences, where the cut-off was designated as an ITT eradication rate of at least 80% [26].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that quadruple therapy consisting of a similar combination of antibiotics and a proton-pump inhibitor has repeatedly been shown to be equally eff ective in spite of the presence of metronidazole resistance when the attention was given to the dose of metronidazole (e.g. 400 or 500 mg three times daily) and duration of therapy of approximately 14 days [47][48][49][50][51][52]. So, metronidazole-containing quadruple therapy may have overcome metronidazole resistance to some degree in our studies.…”
Section: Discussionmentioning
confidence: 99%